SOROPREVALÊNCIA DE LEISHMANIOSE VISCERAL CANINA E RELAÇÃO ENTRE SUBCLASSES DE IgG E SINTOMATOLOGIA CLÍNICA - Almeida, João Freitas de (2006)
The Vila Nova town located in the municipality of Raposa, Maranhão, has been reported as endemic area for visceral leishmaniasis. Knowing the importance of dogs as reservoir household, this study aimed to identify the dogs for leishmaniasis infected through test immunoassay (ELISA). Collections of blood of all dogs resident in the locality were held in the period of February to April 2005, giving a sample of 233 dogs. The results of the ELISA showed that 69 dogs showed positive results, corresponding to a seroprevalence of approximately 29.6% of the dogs of the town.